(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
A deadly virus has forced entire mankind to be confined to their homes. While many businesses were permanently shut, most others are still trying to sustain this less profit-generating period. Numerous workers are facing pay-cuts or job loss. This theoretically implies a major impact on the economies of countries with purchasing power of customers reduced due to lower income and supply chain disruption due to strict curbs. However, industries based on Information Technology, e-commerce, dairy products etc, thrived and continued to meet consumers’ demands. This particular study aims to analyze the impact of COVID-19 on consumer behavior. The impact shall be studied with respect to various parameters such as gender, age, income etc of consumers.